Describing the spoken language skills of typically developing Afrikaans-speaking children using language sample analysis : a pilot study - Van der Linde, Jeannie (University of Pretoria, 2022)
Dissertation (MA (Speech-Language Pathology and Audiology))-- University of Pretoria, 2021.